Communication skills in pharmacy practice : a practical guide for students and practitioners - Beardsley, Robert S.; Skrabal, Maryann Z.; Kimberlin, Carole L. (Philadelphia : Wolters Kluwer, 2020)
'Newly focused on the practical communications skills student pharmacists need for effective practice, this updated Seventh Edition--now in full color-- reflects new ACPE standards, including up-to-date coverage of the PPCP model, co-curricular experiences, interprofessional interaction and collaboration, and professional development. Practical, easy-to-use, and packed with relevant case studies and coverage of the latest advances in the field, this edition is ideal for the foundational course and pre-experiential training. Expanded emphasis on communication skill application helps students master the knowledge and skills they need for pharmacy practice Additional content added on motivational interviewing, e-commerce, contemporary ethical issues (such as medical marijuana and opioid abuse), and student-preceptor and pharmacist-management communication issues Full-color design with new diagrams and figures enhances readability Additional case studies from diverse settings prepare students to deal with the wide range of situations they will encounter in practice Stronger emphasis on assessing communication skills includes coverage of patient surveys and colleague observers Expanded coverage on choosing effective patient education materials and communicating with Limited English Proficiency (LEP) patients prepares students for professional practice Revised review questions, chapter-ending review cases, and references help students master the material Enrich Your eBook Reading Experience with Enhanced Video, Audio and Interactive Capabilities! Read directly on your preferred device(s), such as computer, tablet, or smartphone Easily convert to audiobook, powering your content with natural language text-to-speech Adapt for unique reading needs, supporting learning disabilities, visual/auditory impairments, second-language or literacy challenges, and more '--Provided by publisher.
Includes bibliographical references and index.
Keywords: Pharmacists; Communication; Professional-Patient Relations